Study of Metallic Pollutants in the Northern River of India - Bhagat Singh; Ram Naresh Tyagi; Anil Jindal (Research Perspective on Biological Science Vol. 2, 2025)
Metals load in the riverine system reflects the concentration of toxicants in the water body that acts as a gutter for industrial effluents in and around the Sirsa tributary of the river Sutlej, the lifeline of North India. The inductively coupled plasma mass spectroscopy (ICPMS) was used to detect the concentration of metal load at IIT Delhi and IDMA laboratory, Panchkula. ICPMS is based on the coupling of inductively coupled plasma, as a method of producing ions (ionizations), with a mass spectrometer as a method of separating and detecting ions. ICPMS is a highly sensitive and modern technique for the determination of a range of metals and several non-metals at concentrations below one part per trillion. The application of Metal Index (MI) can be performed to find out the impact of individual metal ions on river water quality and correlate it with health hazards. The Concentration of Metals (Na, Mg, Ca, Zn, Cu, Mn, Fe, Mo, Al, Se) reported at S1, S2, S3 were within permissible Limit of WHO and BIS, but the value of Boron, Mercury and Thallium were exceeded these guidelines constantly at site S2 of study area. The metal index values at S1, S2, and S3 were 1.55, 5.80, and 2.57, respectively. The site S2 was strongly affected due to the presence of elemental dust and untreated wastewater discharged by chemical industrial units of the Baddi region. This site (S2) was nearer to CETP on the bank of the Sirsa river and found to be unsuitable at all with a higher value of metal index. It is to devise indices to estimate drinking water quality with respect to the concentration of metal elements after an equal interval of time; as there may be seasonal changes in the load of debris due to the rate of pollutant dumping in the riverine ecosystem, which is directly proportional to the amount of metal ions.